ANALISIS PEMIKIRAN EKONOMI ISLAM DAULAH MAMLUK DAN KONTRIBUSINYA TERHADAP PERADABAN - Anisa Utami Novianty; Mukhtar Lutfi; Nasrullah Bin Sapa (CV. Adiba Aisha Amira, 2025)
The Mamluks who ruled the Islamic world in the 13th to 16th centuries, played an important role in the history of Islamic civilization, both in terms of politics, economy, social, and culture. This article discusses the history of the formation of the Mamluks, their contribution to Islamic civilization. And the thinkers who made great contributions to the development of thought in that era. The Mamluks were known for successfully maintaining political stability and introducing social-economic reforms that had an impact on the welfare of society. The main contributions of the Mamluks to Islamic civilization include progress in the fields of economics, science, and infrastucture. In addition, thinkers from the Mamluks such as Ibn Taimiyyah who developed a theory on the concept of price, and Al-Maqrizi who developed a theory on the concept of inflation. This study shows that although the Mamluks faced various external and internal challenges, they managed to create significant progress that formed a cultural and intellectual heritage that continues to influence the Islamic world today.